TerraSAR-X observations of Antarctic outlet glaciers in the Ross Sea sector - Jezek, Kenneth; Abdel Jaber, Wael; Floricioiu, Dana (2011 IEEE International Geoscience and Remote Sensing Symposium, 2011)
We discuss TerraSAR-X observations of two Transantarctic Mountain outlet glaciers, Nimrod and Byrd. High resolution TerraSAR-X data acquired over the area in late 2009 and late 2010 using left looking mode were processed to generate detailed 2D ice velocity maps by speckle tracking. The patterns of ice flow from East Antarctica to Ross Ice Shelf are analyzed and compared by means of longitudinal and transverse transects. Detailed knowledge about surface velocity is crucial for estimating the magnitude of ice flux and understanding the dynamics East Antarctica fast glaciers that discharge into the Ross Ice Shelf.